2023
DOI: 10.1007/s00431-023-04982-6
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of pediatric inpatients and outpatients with COVID-19: a point prevalence study from Turkey

Abstract: This multi-center point prevalence study evaluated children who were diagnosed as having coronavirus disease 2019 (COVID-19). On February 2nd, 2022, inpatients and outpatients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were included in the study from 12 cities and 24 centers in Turkey. Of 8605 patients on February 2nd, 2022, in participating centers, 706 (8.2%) had COVID-19. The median age of the 706 patients was 92.50 months, 53.4% were female, and 76.7% were inpatients. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In 2022, the two most prevalent symptoms were fever and cough, accounting for 89.4% and 73.9%, respectively, as reported in the majority of research [ 17 , 19 ]. Lu et al found that the most common clinical symptoms were cough (52%), fever (41%), pharyngitis (46%), diarrhea (9%), and vomiting (6%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, the two most prevalent symptoms were fever and cough, accounting for 89.4% and 73.9%, respectively, as reported in the majority of research [ 17 , 19 ]. Lu et al found that the most common clinical symptoms were cough (52%), fever (41%), pharyngitis (46%), diarrhea (9%), and vomiting (6%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our median age is much lower compared to other studies. Yılmaz et al noted that the median age of SARS-CoV-2 patients in Türkiye in 2022 was 92.5 months [ 17 ]. COVID-19-associated hospitalization was defined as any person who tested positive for SARS-CoV-2 while admitted to our hospital.…”
Section: Discussionmentioning
confidence: 99%